QT Interval Dispersion as a Predictor of Clinical Outcome in Acute Ischemic Stroke - Tang, Hefei; Sun, Jiayao; Wang, Yu; Jie, Xu; Ma, Yan; Wang, Anxin; Zhang, Yijun; Wang, Xingao; Wang, Yongjun (Frontiers in Neurology, 2021)
Background and Purpose: QT dispersion (QTd) abnormalities are widely documented in stroke patients. This study aims to investigate the association between QTd and clinical outcomes in IS patients. Methods: IS patients registered in the Blood Pressure and Clinical Outcome in transient ischemic attack (TIA) or IS (BOSS) registry between 2012 and 2014 within 24 h of onset were analyzed. In this prospective observational study, we identified 1,522 IS cases with adequate electrocardiographic evaluations to assess QTd after the index stroke. Patients were classified into four groups based on the quartile of QTd, with the lowest group as the reference. The primary stroke outcome was defined as a modified Rankin Scale score ≥3 at 1-year. Multiple logistic regressions were utilized to investigate the association between QTd and outcome events. Results: The mean QTd across all cases was 57 ms (40–83). Functional dependency or death was documented in 214 (14.98%) cases at 1 year. After adjusting for confounders, the prevalence of death and major disability (mRS ≥ 3) showed significant differences according to the quartile of QTd, with the risk of death and major disability (mRS ≥ 3) at 1 year being significantly higher for patients in Q4 than for those in Q1 (adjusted OR = 1.626, 95% CI:1.033–2.560). However, there were no significant correlation between QTd and the event outcomes at 1 year. Conclusions: QTd was associated with poor functional outcomes at 1 year. QTd is a useful surrogate marker for adverse functional prognosis, which might help to stratify risk in patients with acute IS.